Pengaruh Lokasi Terhadap Keputusan Pembelian: Studi Kasus Kantin UIN Sumatera Utara - Sugeng Arifandi Banurea; Siti Aisyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
North Sumatra UIN canteen is a business located in a UIN North Sumatra campus area, this canteen is a gathering place for students during breaks. This study aims to determine how much influence the location has on purchasing decisions that will be made by consumers. This study uses data collection methods from questionnaires and interviews with UIN North Sumatra students who have eaten and stopped at the canteen. From the results of this study, it can be concluded that the locations are very influential on purchasing decisions that will be made by consumers